Reliquaries and Athropomorphic Imagination - Munk, Ana (2013)
The presentation examined reliquaries as anthropocentric and anthropomorphic objects, that is, as artworks that primarily engage with the human body. In the broadest sense, anthropomorphism can be defined as a cultural practice by which sacred is made human-like. The issue of appropriatness of artistic and technological upgrading of sacred remains was discussed in the Middle Ages and was reexamined in this presentation from the point of view of current theoretical approaches.